An increasing, potentially measles-susceptible population over time after vaccination in Korea. Issue 33 (24th July 2017) - Kang, Hae Ji; Han, Young Woo; Kim, Su Jin; Kim, You-Jin; Kim, A-Reum; Kim, Joo Ae; Jung, Hee-Dong; Eom, Hye Eun; Park, Ok; Kim, Sung Soon
Highlights: Measles-specific antibodies wane in the absence of boosting by the wild-type virus. The number of potential measles-susceptible individuals progressively accumulates. Vaccine-induced immunity is less effective than naturally acquired immunity. Abstract: Background: In Korea, measles occurs mainly in infants <12 months of age, who are unvaccinated. In addition, vaccine populations, including adolescents and young adults, can become infected though importation. Thus, the question arises whether the current level of herd immunity in Korea is now insufficient for protecting against measles infection. Methods: Age-specific measles seroprevalence was evaluated by performing enzyme immunoassays and plaque reduction-neutralization tests on 3050 subjects aged 0–50 years (birth cohort 1964–2014) and 480 subjects aged 2–30 years (birth cohort 1984–2012). Results: The overall seropositivity and measles antibody concentrations were 71.5% and 1366 mIU/mL, respectively. Progressive decline in antibody levels and seropositivity were observed over time after vaccination in infants, adolescents, and young adults. The accumulation of potentially susceptible individuals in the population was confirmed by comparing data from 2010 and 2014 seroprevalence surveys. The statistical correlation between measles incidence and measles seronegativity was determined. Conclusions: Waning levels of measles antibodies with increasing time post-vaccination suggests that measles susceptibility is potentially increasing in Korea. This trend may be related to limitations of vaccine-induced immunity in the absence of natural boosting by the wild virus, compared to naturally acquired immunity triggered by measles infection. This study provides an important view into the current measles herd immunity in Korea.